Functional beverage development from traditional Thai polyherbal tonic: Antioxidant-rich microcapsules and comprehensive sub-chronic toxicity assessment - Thammarat Kaewmanee; Acharaporn Issuriya; Piyapong Choochana; Pinanong Na-Phatthalung; Surasak Limsuwan; Sasitorn Chusri (PLoS ONE, 2025)
This study aimed to optimize microencapsulation conditions for Phy-Blica-O (PBO), a traditional Thai polyherbal tonic, and to assess the safety of its consumer-accepted herbal tea formulation, Phy-Blica-D (PBD). PBO decoction and its phenolic-rich extract were spray-dried at different inlet temperatures (140°C, 180°C) and maltodextrin-gum Arabic ratios. Encapsulation efficiency was highest at 140°C with maltodextrin alone, while antioxidant activity was greatest in microcapsules prepared at 180°C with a 6:4 maltodextrin to gum Arabic ratio, as shown by DPPH, ABTS, and FRAP assays. PBD demonstrated strong in vitro antioxidant activities and was subsequently assessed in a 90-day subchronic toxicity study in Wistar rats. No treatment-related mortality, clinical abnormalities, organ toxicity, or hematological or biochemical disruptions were seen at doses up to 300 mg/kg/day, indicating a NOAEL above this level. These findings suggest that optimized PBO microcapsules and the PBD tea blend are safe, antioxidant-rich functional ingredients with strong potential for commercialization in complementary and integrative medicine.